2021
DOI: 10.3390/ijerph18179376
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Smoking Cessation Smartphone App (Quit with US) for Young Adult Smokers: A Single Arm, Pre-Post Study

Abstract: While smartphone applications (apps) have been shown to enhance success with smoking cessation, no study has been conducted among young adult smokers aged 18–24 years in Thailand. Quit with US was developed based on the 5 A’s model and self-efficacy theory. This single arm, pre-post study was conducted aiming to assess results after using Quit with US for 4 weeks. The primary outcome was a biochemically verified 7-day point prevalence of smoking abstinence. The secondary outcomes included smoking behaviors, kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…Additional information of the smartphone apps’ design and development was described in detail elsewhere [ 32 ]. Briefly, Quit with US was intentionally invented in Thai for iOS and Android operating systems to encourage smoking cessation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional information of the smartphone apps’ design and development was described in detail elsewhere [ 32 ]. Briefly, Quit with US was intentionally invented in Thai for iOS and Android operating systems to encourage smoking cessation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, use of Quit with US outcome was assessed by only participants in the intervention group at the 12-week follow-up. Information regarding the questionnaire development was described in detail elsewhere [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies did not mention shared decision making; however, similar concepts and strategies could be taken into consideration. Two studies regarding adolescent smoking cessation using text message and smartphone apps showed a positive effect and a cessation rate of 31% using an interactive, supportive, self-motivating design, which are important features [18,19]. A recent systematic review highlighted the principles and effectiveness of multiple behavioral interventions and personalized counseling, which are also important in our SDM model [17].…”
Section: Introductionmentioning
confidence: 99%